A 3D/0D cobalt-embedded nitrogen-doped porous carbon/supramolecular porphyrin magnetic-separation photocatalyst with highly efficient pollutant degradation and water oxidation performance. (10th October 2022) - Ning, Lufang; Xu, Jing; Lou, Yang; Pan, Chengsi; Wang, Zhouping; Zhu, Yongfa
Highlights: Cobalt-embedded nitrogen-doped porous carbon (Co-N-C)/supramolecular porphyrin (SA-TCPP) magnetic-separation photocatalyst was prepared. SA-TCPP nanocrystals were well deposited on Co-N-C nanocubes to establish a 3D/0D heterostructure. SA-TCPP and Co-N-C were self-assembled via π-π interaction, hydrogen bonding and chemical bonding. The synergistic effect between Co-N-C and SA-TCPP endowed Co-N-C/SA-TCPP with enhanced light utilization, accelerated charge migration and well recyclability. Co-N-C/SA-TCPP displayed dramatically improved pollutants degradation and water oxidation activities. Abstract: A 3D/0D cobalt-embedded nitrogen-doped porous carbon nanocubes (Co-N-C)/supramolecular tetra (4-carboxylphenyl) porphyrin nanocrystals (SA-TCPP) photocatalyst was successfully self-assembled via π–π interaction, hydrogen bonding, and chemical bonding. Co-N-C/SA-TCPP heterostructure exhibited satisfactory visible photocatalytic oxidation performance on pollutant degradation and water evolution. The degradation rates of Co-N-C/ST (30%) composite towards 2, 4-dichlorophenol, ofloxacin, and ethylene were 10.9, 7.2, and 2.1 times faster than SA-TCPP, respectively. The oxygen evolution efficiency was 1.9 times higher than SA-TCPP. The remarkably improved oxidation activities of Co-N-C/SA-TCPP were mainly ascribed to the following reasons: (1) Co-N-C could enhance the light absorption ability of SA-TCPP to produce more photoinduced carriers. (2) The well-developed porosity of Co-N-C could optimize the dispersibility of SA-TCPP to provide more reactive sites and charge separation channels. (3) The π–π interaction between SA-TCPP and Co-N-C was beneficial to interlayer charge mobility, while the embedded cobalt nanoparticles (Co NPs) and N-doped carbon matrix could serve as electron traps to accelerate interfacial electron transfer. Additionally, the ferromagnetic Co NPs endowed Co-N-C/SA-TCPP with magnetic-separation function to promote recyclability in practical application.